On boundedness of square means for the logarithms of Blaschke products - Kondratyuk, Ya. V.; Kondratyuk, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish conditions for boundedness of square means of the logarithms of Blaschke products.